In vitro induction of NETosis: Comprehensive live imaging comparison and systematic review. - Tamara Hoppenbrouwers; Tamara Hoppenbrouwers; Anouchska S A Autar; Andi R Sultan; Tsion E Abraham; Wiggert A van Cappellen; Adriaan B Houtsmuller; Willem J B van Wamel; Heleen M M van Beusekom; Johan W van Neck; Moniek P M de Maat (PLoS ONE, 2017)
Background Multiple inducers of in vitro Neutrophil Extracellular Trap (NET) formation (NETosis) have been described. Since there is much variation in study design and results, our aim was to create a systematic review of NETosis inducers and perform a standardized in vitro study of NETosis inducers important in (cardiac) wound healing. Methods In vitro NETosis was studied by incubating neutrophils with PMA, living and dead bacteria (S. aureus and E. coli), LPS, (activated) platelets (supernatant), glucose and calcium ionophore Ionomycin using 3-hour periods of time-lapse confocal imaging. Results PMA is a consistent and potent inducer of NETosis. Ionomycin also consistently resulted in extrusion of DNA, albeit with a process that differs from the NETosis process induced by PMA. In our standardized experiments, living bacteria were also potent inducers of NETosis, but dead bacteria, LPS, (activated) platelets (supernatant) and glucose did not induce NETosis. Conclusion Our systematic review confirms that there is much variation in study design and results of NETosis induction. Our experimental results confirm that under standardized conditions, PMA, living bacteria and Ionomycin all strongly induce NETosis, but real-time confocal imaging reveal different courses of events.